Implementation of Standard Sanitation Operating Procedure in the process Stik Jaleee making in UMKM Kube Amanah Samarinda - Rusdin, Ilmiani; Sulistiawati, Septiana; Kusumaningrum, Indrati (Journal of Agritechnology and Food Processing, 2023)
Sanitation Standard Operating Procedure (SSOP) is an important step that plays a role in maintaining the quality of a food product and fulfilling food safety guarantees according to standards. There are 8 key aspects of SSOP that must be met by a food business unit to produce good product quality and safety. The purpose of this study was to determine the application of SSOP in the production of Stik Jaleee at UMKM Kube Amanah Snack Samarinda. The method used in this research is descriptive qualitative with primary data collection through observation, interviews and active participation. The production process of Stik Jaleee includes the preparation of raw materials, weighing, grinding, mixing ingredients, printing, frying, draining, sorting and packaging. The results of this study indicate that the application of 8 key aspects of SSOP has not been fully implemented in Kube Amanah. Aspects that have been implemented according to the SSOP key are water safety, condition and cleanliness of surfaces in contact with food, protection or protection from chemicals, labelling and storage, employee health and pest control. Aspects that have not been properly implemented are the prevention of cross-contamination and the provision of hand washing, sanitation and toilet facilities.